Modeling and simulating the dynamics of the "Death Star" shotgun target - Brown, A. A. (Sports Engineering, 2017)
Modern competitive shooting is a strenuous test of the human perceptual and motor systems. Like driving a race car or piloting a high performance aircraft, speed shooting matches require precise, rapid movements coordinated using a careful mixture of planning and reaction. In some disciplines of competitive shooting, this mixture is further complicated by complex moving targets. This paper develops a set of state space equations for a moving, reactive steel target used in professional 3-Gun competition. The equations for target motion are nonlinear, time-varying, and chaotic in certain regions of the state space. Once derived, the equations for target motion are validated against motion extracted from video. Then, the calibrated equations are implemented in real-time on a portable, laser-activated simulator. Applications of the simulation environment to marksmanship training and human motor control studies are also discussed.